Más allá del pensamiento abismal, hacia las teorías generales de la salud: Aprendizajes del COVID-19 - Saleh, Marwa (2023)
My growing restlessness as a biomedical doctor drew me to anthropology, and to the study of labels in the COVID-19 pandemic health spectrum, so I may start understanding the complexity of health care beyond my clinical work. In this study I conduct field work at 4 distinct sites, with the methods of interviewing, focus groups and participant observation. The physical sites included Pano, a Kichwa town in the Ecuadorian Amazonia, at AMUPAKIN a Kichwa midwife-led health center near Pano in the Amazonia, and in Santa Rosa, a village in the coastal province of Santa Elena in Ecuador.